(3OjhGf GdCOHs - (3ESMGb Hf EHQGgje Hf GdMSjf GdaGQGHqj, CHh EHQGgje, J (B350 (3g` s
(3BNQgG (B:s
(3hGYdfcS GdQCS EPG GTJO ShGOg hjbGd (B: (3GaQfbYhG Ci GfcTahG , hGbQfHY Ci GLJeY hTYQ eSMfcc Ci TOjO GdShGO heYdfcc Ci cKja eLJeY s
(3fSNI jJab ChdgG eY Chd fSNI edi edc (B- (3WgQGf (B345 (3HGNJdGa ai HYV GdCdaXs
(3GdNW eged GdfbW CMjGfGs
(3HOGNdgG ChQGb cJHJ SfI (B758 (3g` s
(3cJHJ GdYfhGfGJ HGdMeQI YdjgG ebGHdGJ s
(3hHgG SbWs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GddZIs